Potency moringa oleifera on perineal wound healing - Yulia Fitri; Putri Santy (Science Midwifery, 2023)
Complications perineal wound can cause morbidity on significant mother including painful chronic , infection , shame , depression , loss function sexual and in condition more heavy cause incontinence defecate .Moringa Oleifera contain compound stimulating phytochemicals healing wound . This study aims to determine influence gift capsule Moringa oleifera on healing time mother's perineal wound childbirth . Design used is Quasi Experimental with nonrandomized pretest-posttest design. The research sample is 30 mothers childbirth (15 case groups and 15 control groups). Giving capsule Moringa 500 mg/day for 10 days . Measurement healing wound done 2 times ie day to 3 and day to 5 post partum with use REEDA scale . Data analysis using the T test. The results of the study showed the provision of capsules Moringa 500 mg for 5 days post partum significantly accelerated healing wound perineum (P=0.00). Moringa can accelerate healing post perineal wound childbirth . Further research is needed regarding about content potential compound active especially those who play a role in healing wound.Complications perineal wound can cause morbidity on significant mother including painful chronic , infection , shame , depression , loss function sexual and in condition more heavy cause incontinence defecate .Moringa Oleifera contain compound stimulating phytochemicals healing wound . This study aims to determine influence gift capsule Moringa oleifera on healing time mother's perineal wound childbirth . Design used is Quasi Experimental with nonrandomized pretest-posttest design. The research sample is 30 mothers childbirth (15 case groups and 15 control groups). Giving capsule Moringa 500 mg/day for 10 days . Measurement healing wound done 2 times ie day to 3 and day to 5 post partum with use REEDA scale . Data analysis using the T test. The results of the study showed the provision of capsules Moringa 500 mg for 5 days post partum significantly accelerated healing wound perineum (P=0.00). Moringa can accelerate healing post perineal wound childbirth . Further research is needed regarding about content potential compound active especially those who play a role in healing wound.Complications perineal wound can cause morbidity on significant mother including painful chronic , infection , shame , depression , loss function sexual and in condition more heavy cause incontinence defecate .Moringa Oleifera contain compound stimulating phytochemicals healing wound . This study aims to determine influence gift capsule Moringa oleifera on healing time mother's perineal wound childbirth . Design used is Quasi Experimental with nonrandomized pretest-posttest design. The research sample is 30 mothers childbirth (15 case groups and 15 control groups). Giving capsule Moringa 500 mg/day for 10 days . Measurement healing wound done 2 times ie day to 3 and day to 5 post partum with use REEDA scale . Data analysis using the T test. The results of the study showed the provision of capsules Moringa 500 mg for 5 days post partum significantly accelerated healing wound perineum (P=0.00). Moringa can accelerate healing post perineal wound childbirth . Further research is needed regarding about content potential compound active especially those who play a role in healing wound.Complications perineal wound can cause morbidity on significant mother including painful chronic , infection , shame , depression , loss function sexual and in condition more heavy cause incontinence defecate .Moringa Oleifera contain compound stimulating phytochemicals healing wound . This study aims to determine influence gift capsule Moringa oleifera on healing time mother's perineal wound childbirth . Design used is Quasi Experimental with nonrandomized pretest-posttest design. The research sample is 30 mothers childbirth (15 case groups and 15 control groups). Giving capsule Moringa 500 mg/day for 10 days . Measurement healing wound done 2 times ie day to 3 and day to 5 post partum with use REEDA scale . Data analysis using the T test. The results of the study showed the provision of capsules Moringa 500 mg for 5 days post partum significantly accelerated healing wound perineum (P=0.00). Moringa can accelerate healing post perineal wound childbirth . Further research is needed regarding about content potential compound active especially those who play a role in healing wound.